THE USE OF WORDS FROM THE ARABIC LANGUAGE IN THE POEM "INSON" - Abdurahmon Kayumdjanovich Latipov; Xolmuhammad Xayrulloyevich Fattohov (Galaxy International Interdisciplinary Research Journal, 2021)
This article examines the semantic aspects of some words from the Arabic language used in Erkin Vahidov’s poem "Man". It deals with issues related to the poet’s skill in the use of words, his views based on the inner meanings of words.